2007
DOI: 10.1007/bf03194658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variants in the ovine skeletal-muscle-specific calpain gene on body weight

Abstract: The ovine skeletal-muscle-specific calpain gene (p94), which is known also as the n-calpain or calpain 3 gene (CAPN3), was screened with primers. Selection of the PCR primers was based on the ovine cDNA sequence (GenBank accession No. AF087570). After sequence alignment between the ovine and human (AY902237) genes, exon and intron boundaries were determined. Polymorphisms were observed in the intron region for the CAPN31112 and CAPN31213 segments, and the sequences for these segments were submitted to the GenB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…There are few studies linking CAPN3 genotypes to growth traits and market retail cuts of lambs. These studies reported that CAPN3 polymorphisms were associated with increased (11.8 to 13.3%) lamb birth weight (Chung et al, 2007), increased (1.8 to 2.4%) leg weight (Bickerstaffe et al, 2008) and increased shoulder weight and hot carcass weight (Fang et al, 2013). In our study, we found that polymorphisms in CAPN3 gene had significant association with post-weaning daily gain, marketing weight and lean meat%.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…There are few studies linking CAPN3 genotypes to growth traits and market retail cuts of lambs. These studies reported that CAPN3 polymorphisms were associated with increased (11.8 to 13.3%) lamb birth weight (Chung et al, 2007), increased (1.8 to 2.4%) leg weight (Bickerstaffe et al, 2008) and increased shoulder weight and hot carcass weight (Fang et al, 2013). In our study, we found that polymorphisms in CAPN3 gene had significant association with post-weaning daily gain, marketing weight and lean meat%.…”
Section: Resultssupporting
confidence: 65%
“…In sheep, a single nucleotide polymorphism (SNP) in intron 11 of CAPN3 gene has been associated with birth weight (Chung et al, 2007), and the yield of retail lamb meat cuts (Bickerstaffe et al, 2008). The allelic variants, which detected in exon 10 by Fang et al (2013), were found to be associated with shoulder weight and hot carcass weight (P< 0.05).…”
mentioning
confidence: 99%
“…Quantitative traits such as average daily gain (ADG) or final body weight are controlled by a great number of genes. Several genes such as growth hormone (GH), leptin, calpain, and calpastatin are considered as genetic candidate markers for growth rate and meat production traits in mammalian (Chung et al, 2007;Marques et al, 2006;Nassiry et al, 2007;Zhou et al, 2009). Investigation into the relationship between these genetic markers polymorphism and ADG of lambs may lead to design a more efficient selection program.…”
Section: Introductionmentioning
confidence: 99%
“…The SSCP pattern showed three allele sequences of CAPN3 in sheep, and single nucleotide polymorphism (SNP) was identified at exon 10 [ 1 ]. Furthermore, CAPN3 SNP on intron 11 was found to be associated with birth weight in sheep [ 4 ].…”
Section: Introductionmentioning
confidence: 99%